Biodelinification as Pretreatment to Acid Hydrolysis of Oil Palm Trunk (OPT) : Kinetic Study - Wan Nur Atiqah, Wan Yusoff (2013)
Acid hydrolysis is important to breakdown cellulose into its constituent sugar such as glucose. Biodelignification is one example of pretreatment. Pretreatment is applied to make the cellulose accessible to hydrolysis for further conversion such as sugar. Kinetic study is important to determine kinetic parameter for production of glucose by acid hydrolysis. The main purpose of this research is to study kinetic acid hydrolysis of OPT to produce glucose. The methodology of this research can be summarized as follow. Firstly, for untreated OPT, the research is started by run acid hydrolysis to OPT. Two stage of acid hydrolysis is applied. In this method, first, OPT is submerged in 60% sulfuric acid for 30 min and respectively at 60°C. Next, OPT is applied with 30% acid hydrolysis for 60 min and respectively at 80°C. For treated OPT, biodelignification is applied to OPT and continued with acid hydrolysis as mentioned in untreated OPT. Optimum conditions for biodelignification is as follow: temperature at 25.16°C, 7.54 pH values, 2.38 mL/12 hour moisture content and 1:2 fungi to medium ratio. RK fourth order is used to solve ordinary differential equation and the kinetic parameter obtained is analyzed. K1, K2 and Ymax are the kinetic parameters in this study which means K1 is biomass decomposition rate, K2 is sugar release rate and Ymax is glucose production. After analyze data, kinetic parameters value for treated OPT are Ymax = 5.266 g/l, K1 = 0.011454 min-1 and K2 = 0.015036 min-1 whereas for untreated OPT is Ymax = 4.878 g/l, K1 = 0.007774 min-1 and K2= 0.012584 min-1. For conclusion, results showed that acid hydrolysis with biodelignification pretreatment give better result of kinetic parameter value this is because treated OPT have higher value of K1, K2 and Ymax. High value of K1 means high rate to degrade biomass to produce glucose whereas high value of K2 means that the faster time needed to achieve glucose production and high value of Ymax shows high glucose production. For future study, quantity of glucose obtained can be maximized by using this kinetic parameters obtained.